Solid Phase Synthesis of Isoxazole and Isoxazoline-carboxamides via [2+3]-Dipolar Cycloaddition Using Resin-bound Alkynes or Alkenes - Dadiboyena, Sureshbabu (2012)
An efficient approach for the parallel solid phase synthesis of isoxazole and isoxazoline derivatives has been developed. The isoxazoles and isoxazolines were constructed through a 1,3-dipolar cycloaddition reaction of nitrile oxides, with resin-bound alkynes or alkenes. The cycloaddition reaction conditions performed on solid phase supports was optimized, and an array of resin bound carboxylic acid building blocks were utilized for distinct conversions. This methodology presents a new alternative to the diversity oriented synthesis of disubstituted isoxazoles and isoxazolines different from existing routes which are limited in structural diversity